Biodex© training post-stroke for postural stability in the upper trunk: A pilot study - Helena W. Nel; Witness Mudzi; Elizabeth C. Janse van Vuuren; Eustasius Musenge (AOSIS, 2020)
Background: Stroke affects upper trunk postural stability and upper limb function in approximately 85% of stroke survivors. Upper trunk postural stability is essential for functioning of the upper limb and is a prerequisite for hand function. The rehabilitation of the upper limb and upper trunk post-stroke remains a challenge because of poor recovery of motor and sensory function. Objectives: To determine the effect of Biodex© upper limb weight-bearing training on upper trunk postural stability in patients post-stroke. Method: A longitudinal randomised control pilot trial with single blinding was undertaken to assess postural stability on the Biodex© at baseline and 1-month post-baseline. In addition to standard rehabilitative care, upper limb weight-bearing training on the Biodex© was added for participants in the experimental group. Descriptive data analysis and the Mann-Whitney test for group comparisons were done using STATA (p 0.05). Results: Fifteen participants took part, seven in the control and eight in the experimental group, with an overall median age of 55 years. At baseline there were statistically significant lower scores in the experimental group on overall (p = 0.02) and anterior/posterior (p = 0.009) stability level 6 (moderately unstable base of support) in the upper trunk postural stability scores. No statistically significant improvements were noted between groups on any of the Biodex© stability levels at 1-month post-baseline testing (p 0.05). Conclusion: Upper limb weight-bearing training with the addition of Biodex© training did not result in improvements in upper trunk postural stability. Clinical implications: The findings suggest that exercising on a moderately unstable base of support may improve upper trunk postural stability in patients post-stroke. The addition of Biodex© training to standard rehabilitative care for retraining and exercising upper trunk postural control in a weight-bearing position does not lead to better outcomes than standard care.